(untitled) (TEST Ticontre. Theory Text Translation, 2020)
Abstract As a tribute to the poet, we propose a primordial reading about the Valente`spoetry to do an exercise of approximation to understand the poem having onlythe materials offered by the poet. In this case we will dispense with a traditionalcritical support and our references will just be his own bibliography.